Application Method Simple Multi-Attribute Rating The Technique (SMART) At Selection Receiving Scholarship Tahfidz - Usna Widayanti; Kusuma Hati (IAIC International Conference Series, 2020)
The Tahfidz Scholarship is a development program for Mahfouz centers in the community, community, educational institutions, and installations. The aim is to form and print Al-Quran memorizers. So far, the system used to determine the selection of scholarship recipients is by selecting one by one the data and values ??of the applicants. So that it can cause errors in the final selection stage. In addition, if you still use manual methods, there is a concern that the selection of prospective scholarship recipients will not be conducted objectively. So use of a computer-based Decision Support System can be used as a solution to facilitate decision making. The method used in this study is the Simple Multi-Attribute Rating Technique (SMART). The purpose of this study was to facilitate the Tahfiz Center (RTC) Research and Development section in selecting prospective Tahfidz scholarship recipients. From the results of this study, it is hoped that the Simple Multi-Attribute Rating Technique (SMART) method can be implemented in the Scholarship Recipient Selection Decision Support System with the output of data on scholarship recipients who received assistance from the Tahfiz Center (RTC) House.